Natural vibrations of a composite plate strip with macrocracks - Rzayev, OG; Akbarov, SD (CONSULTANTS BUREAU, 2002)
The fundamental frequency of a clamped composite plate strip with either one free macrocrack or two parallel free cracks is determined using the exact equations of the theory of elasticity. The plate is assumed made of an anisotropic orthotropic material with effective mechanical properties. The problem is solved by the finite-element method. Numerical examples are given to demonstrate how the problem parameters influence the fundamental frequency.
Keywords: RECTANGULAR-PLATES; BEAMS; Mechanics